INDONESIA’S NATURAL GAS: PRODUCTION, RESERVES, AND CHALLENGES - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2007)
Recent years has witnessed decline in national oil production at an alarming rates of higher than 10% annually. On the other hand, national gas reserves and production situation is much better even though problems such as unanticipated production shortfall of existing fields and commerciality of new reserves have still to be faced. Analysis on history of production and reserves and comparison between oil and gas discoveries in recent years may lead into a conclusion natural gas may serve as an alternative source for energy and national income in years ahead. However, challenges such as technology, infra-structures, law enforcement, social unrests, tight regulations, and incentives are still day-to-day reality. These challenges need to be addressed appropriately if sustainable gas, and also oil, productions are to be achieved.